How and why Does the Disclosure of Edgar Filings Differ Among US-Listed Firms? An Empirical Investigation - Dimmer, Michael (Eurasian Business and Economics Perspectives, 2021)
This empirical investigation aims to examine whether the disclosing behavior of companies listed in the United States differs depending on their financial performance. The results are based on a sample of 1,726,654 filings from 3440 companies submitted in the EDGAR database of the SEC between 2010 and 2018. The sample is divided into two groups using accounting variables and market data as separating features. The financial reports are also categorized. The analyses focus on filings of the categories insider trading, non-timely filings, and amendments. A Mann-Whitney U-test is used to test the difference between the reporting behavior of companies and their financial performance. The results show that there is a statistically highly significant difference, which thus explains the dependence of the submission behavior and the financial performance of companies. The trend stays robust to adjustments to the research design. The outcomes demonstrate how important the interaction between filings is. In addition to analyzing the content of an individual filing of a company, the findings suggest that the frequency and type of filings of a company also needs to be considered. Consequently, future research should increasingly analyze the interaction of the individual submissions.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Data analysis; EDGAR; Financial disclosure; Reporting behavior; SEC filings